Hometown Lending - Lim, Ivan; Nguyen, Duc Duy (Journal of Financial and Quantitative Analysis, 2021)
Abstract Banks open more branches and make more lending near their CEOs’ childhood hometowns. The effects are stronger among informationally opaque borrowers and among CEOs who spend more time in their childhood hometowns. Furthermore, loans originated near CEOs’ hometowns contain more soft information and have lower ex post default rates, implying that hometown loans are more informed. Hometown lending does not affect aggregate bank outcomes, suggesting that credit is being reallocated from regions located farther away to regions proximate to bank CEOs’ hometowns.